A study of the metrological characteristics of multisensor systems for measuring external magnetic fields - Degtiarov, O. V.; Klyuchnyk, I. I.; Khoroshailo, I. E.; Lutsenko, V. O. (ХНУРЕ, 2025)
The paper investigates the metrological characteristics of instruments for spatial harmonic analysis of external magnetic fields generated by technical objects. Mathematical models of signal conversion are presented, along with relations for calculating the conversion function, sensitivity, linear-angular, and multipole measurement errors. The influence of the spatial configuration of the distributed converter system on measurement accuracy and interference immunity is analyzed. The obtained dependencies can be used to evaluate accuracy and optimize the parameters of spatial harmonic analysis instruments
Keywords: external magnetic field; spatial harmonic analysis; metrological characteristics; distributed converter system; conversion function; measurement error; interference immunity